Perancangan Alat Pendeteksi KWH Meter Berbasis Arduino Uno R3 dan ESP8266 - mufida, ely; Adriansyah , Mochammad Iqbal; Ihsan , Nur Muhammad; Anwar , Rian Septian (LPPM Universitas Bina Sarana Informatika, 2021)
The amount of electrical energy consumption by each consumer can be measured using an electrical energy measuring device, namely the KWH Meter, as used by the State Electricity Company (PLN). Each PLN electricity customer will pay the electricity fee according to the value on the KWH Meter. Electricity customers only know the amount of fees that must be paid and cannot detect or control the electricity consumption for each day. This study aims to create a detection device for electrical energy consumption or KWH Meter that can display electrical power at a certain time in the form of digits. This KWH Meter detection tool is built using the PZEM-004T sensor and Split-CT which is used as a voltage and current sensor, the Arduino Uno R3 microcontroller system which functions to process and process data that has been obtained by the sensor, as well as an LCD and ESP8266 module that will send the results. measurement to the user, and will be displayed on a web-based application. The buzzer will light up when the power used exceeds a predetermined limit to give a warning to the user. This tool can be used by the user to provide information on the use of electricity in a place. The user can set the maximum electricity usage value. If the use of electrical energy exceeds the maximum limit, the buzzer will give a warning, so that the user can control the use of electricity as desired.